Familial Experience With Hirschsprung's Disease Improves the Patient's Ability to Cope - Verkuijl, Sanne J.; Meinds, Rob J.; van der Steeg, Alida F. W.; Sloots, Cornelius E. J.; van Heurn, Ernst; de Blaauw, Ivo; van Gemert, Wim G.; Witvliet, Marieke J.; Vermeulen, Karin M.; Trzpis, Monika; Broens, Paul M. A. (Frontiers in Pediatrics, 2022)
Introduction: Familial occurrence of Hirschsprung’s disease may have a positive effect on patients’ ability to cope with the disease. The aim was to compare long-term bowel function and generic quality of life between patients with familial and non-familial Hirschsprung’s disease. Methods: This was a nationwide, cross-sectional study in which we included all 830 Hirschsprung patients of 8 years and older who had undergone surgery between 1957 and 2015. We excluded patients with a permanent stoma, intellectual disability, or an unknown or foreign address. We requested patients to complete the validated pediatric or adult Defecation and Fecal Continence questionnaire and the Child Health Questionnaire Child Form-87, or the World Health Organization Quality of Life-100 Assessment Instrument. Results: We analyzed 336 Hirschsprung patients, 15.8% of whom were familial cases and 84.2% were non-familial cases. After adjusting for aganglionic length, sex, and age, patients with familial Hirschsprung’s disease were twice more likely to suffer from constipation (OR = 2.47, 95% CI, 1.21 - 5.05, p = 0.013). The quality of life of the pediatric patients was comparable, but in adult patients the energy/fatigue, thinking/learning/concentration, and work capacity facets showed better scores in the familial patients with Hirschsprung’s disease of the rectosigmoid (p = 0.029, p = 0.024, p = 0.036, respectively). Conclusions: Different facets of generic quality of life are better in adult patients with familial Hirschsprung’s disease of the rectosigmoid. It seems that familial experience with the disease influences patients’ coping abilities positively.